Bullying dalam Perspektif Kesehatan, Hukum dan Psikologi (Studi Kasus Santri di Pesantren Kota Jambi) - Wisudariani, Evy; Dony Yusra Pebrianto; Agung Iranda; Fajrina Hidayati; Adila Solida; Andree Aulia Rahmat (Jurnal Kesehatan - STIKes Prima Nusantara, 2024)
Islamic boarding schools, as traditional educational institutions meant to be safe and supportive environments for character building and self-development, have also become places where bullying can occur. This situation highlights the need for serious attention and concrete action from various parties, including educational institutions, parents, communities, and the government, to prevent and address bullying issues both in boarding schools and the broader educational environment. Through a multidisciplinary approach, namely health, law, and psychology, this study aims to identify, analyze, and understand the phenomenon of bullying in boarding schools. This research a quantitative analytical approach with a cross-sectional design. The sample comprises 156 individuals from three boarding schools in Jambi City: As’ad Boarding School, Ainul Yaqin Boarding School, and Darul Hikmah Boarding School. Samples were obtained using a simple random sampling technique. There is a correlation between bullying and mental health among students at the boarding schools in Jambi City in 2024. However, there is no correlation between bullying and emotional intelligence among these students.It is hoped that comprehensive anti-bullying programs can be developed and implemented, along with providing access to counseling and psychological support for students. Additionally, efforts should be made to create a positive environment and a more harmonious atmosphere to reduce the likelihood of bullying.